2012
DOI: 10.1590/s1516-35982012000900018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of forage and feeding behavior of Nellore heifers fed hydrolyzed sugarcane

Abstract: -The objective of this study was to evaluate the chemical characteristics of the forage and ingestive behavior of Nellore heifers fed hydrolyzed sugarcane in different periods of storage. Twenty-four heifers with initial body weight of 119.6±8.1 kg were utilized. The experimental design was completely randomized, in which the treatments were diets with fresh sugarcane and hydrolyzed sugarcane (5 g of lime kg -1 of chopped sugarcane) stored for 24, 48 or 72 hours as the only roughage. The addition of lime to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
4
3
1
1
Order By: Relevance
“…It is noteworthy, moreover, that the treatment of sugarcane with lime did not cause changes in the palatability or acceptability of the forage, fact supported by the feed intake, result contrary to that obtained by MISSIO et al (2013). However, these results confirm those presented in the literature (CARVALHO et al, 2010;MISSIO et al, 2012) which, in most cases, there was no changes in feed intake by the addition of lime to sugarcane. Nevertheless, MISSIO et al (2013) argue that when the treatment of sugarcane with lime increase the fiber digestibility it is expected higher feed intake in diets with hydrolyzed sugarcane in relation to those with fresh sugarcane.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…It is noteworthy, moreover, that the treatment of sugarcane with lime did not cause changes in the palatability or acceptability of the forage, fact supported by the feed intake, result contrary to that obtained by MISSIO et al (2013). However, these results confirm those presented in the literature (CARVALHO et al, 2010;MISSIO et al, 2012) which, in most cases, there was no changes in feed intake by the addition of lime to sugarcane. Nevertheless, MISSIO et al (2013) argue that when the treatment of sugarcane with lime increase the fiber digestibility it is expected higher feed intake in diets with hydrolyzed sugarcane in relation to those with fresh sugarcane.…”
Section: Resultssupporting
confidence: 80%
“…The results obtained in this study were similar to those observed by MISSIO et al (2012), who found that the addition of 5g kg -1 of Ca(OH) 2 to sugarcane and stored for 24, 48 or 72 hours did not change CPI, NDFI and TDNI. However, DIAS et al (2011) evaluating amounts of Ca(OH) 2 (0, 8, 16 and 24g kg -1 ) found higher point for CPI and NDFI for 8g kg -1 of lime, due to increased digestibility of dry matter.…”
Section: ------------------------------------------------------------supporting
confidence: 91%
See 3 more Smart Citations